Energy-efficient vegetable storage facilities using solar and modern cooling technologies - Bobur T. Shodiyev; Akram M. Mirzabaev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: the article discusses energy-efficient technologies for storing vegetables using modern cooling methods and renewable energy sources, in particular solar cooling systems. The current state of industrial cooling in Uzbekistan, which consumes significant amounts of electricity, is analyzed, and a significant increase in demand for cooling is projected by 2050. The main problems of existing systems, such as high energy consumption of equipment and outdated technologies, are presented, and conceptual solutions for increasing the energy efficiency of vegetable storages are proposed. Aim: solar cooling technologies, including electrical and thermal systems, as well as their principles of operation and scope of application are described in detail. Special attention is paid to sorption and adiabatic cooling systems as the most promising for regions with a warm climate. The economic and environmental feasibility of introducing solar cooling systems is substantiated, despite the high cost of initial investments. Methods: a critical analysis shows that after 2030, a significant increase in solar cooling technologies is expected. This is due to the expected reduction in technological costs and an increase in energy costs. The expected increase in the installed capacity of solar cooling systems will be more than 1,000 GW by 2050, or 1.5 EJ per year of solar cooling capacity. Results: the use of modern cooling systems with adjustable compressors and highly efficient fans can reduce energy consumption by 15-25% compared to traditional installations.